Institutionalization of the Human Rights Management, Economic and Social Community in the XXI Century: The Global and Eurasian Trends - Baranov, Pavel P.; Mamychev, Alexey Y.; Ovchinnikov, Alexey I. (International Journal of Economics and Financial Issues, 2016)
The article analyzes the modern paradigmatic change settings on the development of the human rights concepts and ensure social community / solidarity in the context of the global and Eurasian trends. The management institute formation in the Russian society is considered as a necessary condition of providing the main directions of the sustainable development strategy. The formation process and the management main lines as the social institute is characterized. Substantially considered the new forms of public unity, which initiate fundamentally different protection mechanisms and the person rights and freedoms ensuring in the XXI century: either the innovative (neoliberal) forms, where the government is given very small place (i.e. it is perceived as one of actors, participants publicly - legal interaction); or the revolutionary forms - depriving the government of any social value in the future, are formulated. Separately, the authors analyze the Eurasian political and legal project of social inclusion and ensuring the rights, freedoms and interests. The article addressed issues of economic sociology - the interaction of two major areas of social life - economic, social and, respectively, the interaction of two types of processes - economic and social. Keywords: economic sociology, power, state, conservatism, modernization, traditionalism postmodernism, transformation, social institute, institutionalizing management JEL Classifications: D71, H55, M11, K49